Variation in the Grading System: Boon or Bane: Standardizing the Assessment Reports: Overcoming Variations in Grading System (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Affiliate colleges of their State Universities have been provided autonomy to run their courses and assess the Management graduates. As a result Universities, adapt various methods of assessment, most of them use either regression method or interpolation method to estimate the percentages or grades. Although by the method of grading students for their assessment, instead of actual marks it has increased many students’ confidence level, but it has led to variations and hence creating ambiguity, when a third party wants to assign a rank or percentile for large number of students. Input data used for the study is different mark sheets from which the grades of two different universities with same grade are this variation due to the grading of students will not be able to make out the actual marks obtained by the individual student. Due to this approximation of estimating the total marks obtained by a student leads to variation which is boon for few and bane for others. This paper address the nuances faced by the students due to variation while converting grades into actual marks obtained by the students, when not mentioned explicitly in the student’s report card. One of the suggested measures is to standardize the assessment reports across the Country which serves not only all the stakeholders of education industry, but also to the third party.